Formulation and quality characteristics of macaroni substituted with chickpea and banana flour - Nguyen Minh Thuy; Tran Hai Yen; Vo Quoc Tien; Tran Ngoc Giau; Vo Quang Minh; Ngo Van Tai (My University, 2023)
The objective of this study was to develop macaroni products from chickpea and green bananas flours by partial substitution wheat flour in order to improve the nutritional composition of the product in the direction of increasing the content of resistant starch, fiber, ash and high quality protein. Four macaroni formulas were established with the control recipe. In five designed recipes, the amount of flour used was gradually reduced from 100% to 70%, while the amount of chickpea and green banana flour substituted increased from 0% to 16% and 0% to 14%, corresponding. The physicochemical characteristics including cooking quality, microstructure, color and nutritional characteristics of macaroni were evaluated. Sensory evaluation of the products created from the formulations was also carried out. The research results have shown that substituting chickpea flour and green banana flour in macaroni formulations affected the physical and chemical properties of the final product. Among the 5 designed formulations, the F3 formula replacing wheat flour with 13% chickpea flour and 10% green banana flour was selected as this product improved the desired nutritional properties. The macaroni product made from the F3 formula contained higher levels of protein, resistant starch, lipids, ash and fiber than the control sample, while the lower carbohydrates have been noted. The rehydration rates, volume gain and cooking loss of F3 product were recorded at values of 67.3%, 91.45% and 3.77%, respectively. The highest number of sensory assessors preferred (80-100%) to the F3 product compared to the macaroni products made up of the remaining formulations.
Keywords: Recipe; Resistant Starch; Control sample; Food composition and properties